A comparative study of finite element analysis for friction stir welding application - Meyghani, B. (Asian Research Publishing Network, 2016)
Friction stir welding (FSW) is a solid state welding technique that has been used in various industries for joining different materials which are difficult or impossible to be welded by conventional welding methods. Complexity of the geometry and a three dimensional character has made the FSW process complicated in comparison with other techniques. Therefore, theoretical study of FSW is challengeable and the governing equation prediction is challengeable. Finite element analyses of FSW can predict various parameters of the welding processes such as temperature profile, deformations, stresses, residual stress and forces. It can also help to investigate the material behavior, which can be time-consuming by using experiments. The process complexity requires the choice of the best finite element software appropriate to the results to be predicted. This paper has compared different finite element analyses which have been done for the numerical simulation of FSW. The results showed that, ABAQUS®, ANSYS® and FLUENT® software have been the mo common software in those papers which have focused on FSW modeling. In the terms of mechanical properties such as thermo mechanical behavior, strain, stress and friction simulation, models created using ABAQUS and ANSYS have achieved greater accuracy. Figures show that, FLUENT software for simulating material flow and fluid dynamic behavior modeling has been the pioneer software. © 2006-2016 Asian Research Publishing Network (ARPN).